A cross sectional study on internet usage for health information among 18- 49 years in urban Chandigarh - Soni, Tanu; Lakshmi, PVM; Kaur, Manmeet (Indian Journal of Community Health, 2017)
Background: Internet use for health information has increased over the years. However, how people use internet for health needs to be explored. Aims & Objectives: Our study aim was to determine the proportion of people who use internet for health information in the age group of 18-49 years in urban Chandigarh, to document the type of health information sought from Internet, and its association with socio-demographic variables. Material & Methods: Community based cross sectional study was carried out with multistage sampling using simple random and systematic random sampling. Data was collected using pretested semi-structured interview schedule. Results: Out of 262, 60.6 % of participants used the internet for health information. Availability of broadband connection at home and gender were significantly associated (p<0.05) with use of the internet for health information. Conclusion: Internet use for health information could have significant potential, particularly in terms of the general public decision-making and autonomy as has been reflected in the results of the present study. The Internet has become an important tool with the potential to improve information dissemination and health care delivery to consumers.